2005
DOI: 10.1271/bbb.69.592
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Two Solanesyl Diphosphate Synthases fromArabidopsis thaliana

Abstract: Solanesyl diphosphate (SPP) is regarded as the precursor of the side-chains of both plastoquinone and ubiquinone in Arabidopsis thaliana. We previously analyzed A. thaliana SPP synthase (At-SPS1) (Hirooka et al., Biochem. J., 370, 679-686 (2003)). In this study, we cloned a second SPP synthase (At-SPS2) gene from A. thaliana and characterized the recombinant protein.Kinetic analysis indicated that At-SPS2 prefers geranylgeranyl diphosphate to farnesyl diphosphate as the allylic substrate. Several of its featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…The latter is not solely distinct from the AtSPS3 functional network but is also intimately linked to plastids. Although such a model fits with the demonstration that AtSPS2 is targeted to plastids, it conflicts with the previous assumption that AtSPS1 localizes to the endoplasmic reticulum (8,9).…”
Section: Modeling Of Gene Co-expression Network Predicts That Arabidocontrasting
confidence: 81%
See 1 more Smart Citation
“…The latter is not solely distinct from the AtSPS3 functional network but is also intimately linked to plastids. Although such a model fits with the demonstration that AtSPS2 is targeted to plastids, it conflicts with the previous assumption that AtSPS1 localizes to the endoplasmic reticulum (8,9).…”
Section: Modeling Of Gene Co-expression Network Predicts That Arabidocontrasting
confidence: 81%
“…12), and previous studies have indeed confirmed that AtSPS2 is targeted exclusively to chloroplasts (8,9,38,39). The localization of GFP-fused proteins demonstrates that this strict plastid localization holds true for AtSPS1 as long as the cognate gene is expressed under the control of its native promoter.…”
Section: Discussionmentioning
confidence: 52%
“…In the present study, both qRT-PCR and RNA-seq analyses indicated that the relative expression levels of NtSPS1 and NtSPS2 were significantly higher in leaves than in stems and roots (P < 0.05). To date, SPS homologs have been identified in A. thaliana [31][32][33], Hevea brasiliensis [34], Oryza sativa [35], and S. lycopersicum [36]. Hirooka et al [32] cloned two SPS genes from A. thaliana and found that the expression levels of AtSPS1 and AtSPS2 in leaves and stems were significantly higher than those in the roots, which is similar to the expression of NtSPS1 and NtSPS2 observed in the present study (Figure 3).…”
Section: Sps Is a Key Enzyme In Solanesol Biosynthesis In Tobaccosupporting
confidence: 88%
“…As pointed out in the introduction, the enzymes from the mevalonate pathway and particularly those of the isoprenoid biosynthetic route have been assigned to several different compartments in mammals and plants (20-23 Hugueney, 1996;Cunillera, 1997;Sanmiya, 1999;Biardi, 1996;Olivier, 2000;Hirooka, 2005;Leivar, 2005). Only a few enzymes of this pathway have been described in kinetoplastids (Montalvetti, 2001 andPena-Diaz, 2004;Ferella, 2006;Urbina, 2002;Ortiz-Gomez, 2006), and have been located to the glycosome, mitochondria, and cytoplasm (Ferella, 2006;Pena-Diaz, 2004 andOrtiz-Gomez, 2006, respectively).…”
Section: Discussionmentioning
confidence: 99%